2017
DOI: 10.3389/fnhum.2017.00361
|View full text |Cite
|
Sign up to set email alerts
|

Structural Correlates of Reading the Mind in the Eyes in Autism Spectrum Disorder

Abstract: Behavioral studies have shown that individuals with autism spectrum disorder (ASD) have impaired ability to read the mind in the eyes. Although this impairment is central to their social malfunctioning, its structural neural correlates remain unclear. To investigate this issue, we assessed Reading the Mind in the Eyes Test, revised version (Eyes Test) and acquired structural magnetic resonance images in adults with high-functioning ASD (n = 19) and age-, sex- and intelligence quotient-matched typically develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 77 publications
(120 reference statements)
0
6
0
Order By: Relevance
“…Functional and structural neuroimaging work has associated RMET performance with activation/size of the inferior frontal gyrus, middle/posterior temporal regions, and the amygdala/hippocampus in typically developing adults 9194 , although findings may defer in ASD 67,95 . Our results for the RMET highlight subcortical structures as being important across disorders; children with ASD also had associations in the lateral mentalization regions and in the insula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional and structural neuroimaging work has associated RMET performance with activation/size of the inferior frontal gyrus, middle/posterior temporal regions, and the amygdala/hippocampus in typically developing adults 9194 , although findings may defer in ASD 67,95 . Our results for the RMET highlight subcortical structures as being important across disorders; children with ASD also had associations in the lateral mentalization regions and in the insula.…”
Section: Discussionmentioning
confidence: 99%
“…Subcortical structures were segmented using multiple automatically generated templates (MAGeT) and their volumes determined from the segmentation results 66 . For the region of interest analysis, we examined the association between mean thickness/volume measurements and social deficits in both the left and right hemispheres combined, except where previous data suggested significant lateralization effects (i.e., the temporal–parietal region 24,29,67 , the amygdala 68,69 , the dorsal striatum 33 , and the insula 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…To capture key aspects of ToM we operationally defined it as the ability to process complex and social emotional states from eyes, face, and voice, including meaning of spoken sentences and prosody cues. The reading the mind in the eyes test (henceforth, RME; Baron-Cohen et al, 2001 ) is one of the most frequently used tests of advanced ToM in clinical settings with groups with autism, Asperger’s syndrome, and schizophrenia (e.g., Baron-Cohen et al, 2001 ; Browne et al, 2016 ; Sato et al, 2017 ). The widespread use is not limited to populations with social deficits, but the test is also sensitive to cultural differences (e.g., Adams et al, 2010 ) and to individual differences of healthy individuals (e.g., Vellante et al, 2013 ; Preti et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests atypicalities in thalamo-cortical and cortico-cortical functioning in ASD (10), which is supported by the recent findings of particularities in cortico-cortical and thalamo-cortical projections. Studies using structural magnetic resonance imaging (MRI) investigated cortical thickness found gray matter reductions in all cortical regions of adults with ASD (43)(44)(45)(46). Moreover, also using structural MRI, Ecker et al (47) showed that cortico-cortical connectivity was locally and globally reduced in ASD.…”
Section: Lower Eeg Power Differences Across the Scalp During Rem Sleep In Asdmentioning
confidence: 99%